Bioassay of Functional Drink - KoTeJa (Coffee, Sea Cucumber, Ginger) Using Male Mice (Mus musculus l.) - Dewi, Kurnia Harlina; Helmiyetti, Helmiyetti; Ruci, Ruca (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2024)
This study aimed to examine the effect of sea cucumber ginger coffee on the behaviors and libido of the Swiss Webster male mice (mus musculus L.), which has given a functional drink product of sea cucumber ginger coffee (KoTeJa). This study consists of five treatments and each treatment was repeated 5 times repetition. These treatments in this study consisted of a negative control (P0); a positive control (P1) using methyl testosterone; a 2nd treatment (P2) using sea cucumber flour; (P3) for KoTeJa + sugar + creamer; and (P4) ginseng coffee. Observations of the libido were performed on days 0 to 5; on days 7 to 9 for locomotor activity; and on day 12 for the spermatozoa quality performed. The results showed that KoTeJa (P3) provides the best effect on the behavior of libido, with an average of 25 times introduction (on the 3rd day) and 39.25 times (on the 5th day), 6 times of average climbing (on the 3rd day), and 2 times of average coitus (on day 3), at an average of 86 times loops of locomotor activity (day 7), 108.66 loops (day to 8) and 124 loops (day 9), and an indicators of the quality of spermatozoa normality of 60.6%.